Application of multiple NIRS imaging device to the exercising muscle metabolism. Issue 2 (2003) - Miura Miura, Hajime Hajime; McCully McCully, Kevin Kevin; Chance Chance, Britton Britton
Abstract : Near infrared spectroscopy (NIRS) is a developing technique that measures the balance between muscle oxygen consumption and oxygen supply that is noninvasive and potentially portable. Differential absorption of light in the 600−900 nm region detects the changes in small vessel hemoglobin oxygen saturation and blood volume. Recent developments include the combining of multiple light sources and photodetectors to provide "images" of oxygen saturation and blood volume of wide regions of muscle. Using multiple NIRS imaging device, we monitored localized muscle metabolism during various exercises in the field as well as in the laboratory. In healthy subjects, the regional differences in oxygen saturation and blood volume were detected in the medial head of the gastrocnemius muscle during a standing plantar flexion exercise, consistent with differences in intramuscular pressure. Patients with peripheral arterial disease (PAD) showed slower recovery for both oxygenation and blood volume after exercise. Treatment for PAD resulted in improvements in NIRS-measured recovery times. In summary, NIRS devices have the ability to detect and monitor impaired muscle circulation. In addition, NIRS devices with multiple channels have the potential to evaluate the regional differences in oxygen status. Multiple NIRS imaging devices have the potential to play an important role in monitoring exercise prescription and clinical uses.